POOR SANITATION OF ENVIRONMENT INFLUENCES NUTRITION STATUS TO UNDER FIVE YEARS - Puspitawati, Natalia; Sulistyarini, Tri (Jurnal Penelitian STIKES Kediri, 2013)
Nutrition status indirectly effects the economic social factor and directly connected with hygiene sanitation and also with the level of consume and infection. Regulation of development in health is to increasing the degree of health including circumstance of nutrition. This study analyzes the goal which is poor environmental sanitation can affect nutritional status. Design in this study is cross-sectional. The population were toddlers (aged 1-5 years) in RW VI Bangsal village. With a sample of 32 respondents using total sampling. Independent variables environmental sanitation and the dependent variable nutritional status. The data was collected using questionnaire and interview, then analyzed using the linear regression with significant level α≤0,05 of linear regression p=0,111, where p>α which means that Ho is accepted, Ha rejected. There is no correlation between environmental sanitation and nutrition status. It can be concluded that there is no negative verification of poor environmental sanitation toward nutrition status to under five years in RW VI Bangsal village.